LEARNING INTERESTS OF CLASS X STUDENTS IN ENGLISH SUBJECTS IN ONE OF SENIOR HIGH SCHOOLS IN BANDUNG - Lilis Siti Aisyah; Anita Anggraeni; Agung Putri Pratama (PROJECT (Professional Journal of English Education), 2022)
This research is a preliminary study that aims to determine the interest of students in one of SMA in Bandung in learning English. This research uses mix methods (qualitative and quantitative ) based on questionnaire results. The results showed that 32.6% liked English lessons. When English lessons took place the "frequent" and "fair attention" lessons were 14 people each (32.6). Students are also most "often" facing difficulties (30.2%). In the classroom the teacher is "sufficient" to create an atmosphere of teaching and learning (48.8%), and "fair" to provide methods (44.2 %) and" fair "to assist in guiding and solving problems (32.6%). After giving English language instruction to students, the teacher "fair" often gave free tests (34.9%), "often fair" to give homework (30.2%), "quite often" to give tests (39.5%) and "Often" gives a test that is in accordance with the material given (37.2%). Usually the teacher will give a test of improvement if the student gets an unsatisfactory score, from the results of the questionnaire "quite happy" students with remedial (37.2%), "not often" skipping in following remedial (39.5%), "quite often "Students repeated their English lessons after remedial (34.9%) and" quite well "after attending the remedial program, so that they" often "studied harder so they would not take repetition in learning English (34.9%). Teachers should be able to design better learning including planning, learning methods, learning media so that learning is more effective and students are more eager to take part in the process of learning English. Keywords:  Learning Interest, Mix Method, Senior High School